Pengaruh Likuiditas Terhadap Profitabilitas Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia - Pitoyo, Mikha Merianti; Lestari, Henny Setyo (Manajemen Bisnis Kompetensi, 2018)
This research aims to know the influence of liquidity toward profitability. The sample used in this study is a company engaged in the manufacturing companies listed on the Indonesia stock exchange (IDX) of the period of 2011-2015. The independent variable in this study is the current ratio, quick ratio, super-quick ratio, current assets turnover ratio, inventory turnover ratio, and the average collection period towards profitability return on assets (ROA), return on equity (ROE), return on capital and the self-employed (ROCE). The number of samples used in the study total 83 manufacturing companies by using purposive sampling. The results of empirical research using the method of regression analysis of the data panel. The results of this research indicate that the variable super-quick ratio/cash ratio has a significant negative influence towards profitability return on assets (ROA) and inventory turnover ratio has a significant negative influence towards profitability return on capital (ROCE) self-employed, while the current ratio, quick ratio, super-quick ratio, current assets turnover ratio, inventory turnover ratio, and the average collection period has no effect on the profitability of the return on assets (ROA) , return on equity (ROE), return on capital and the self-employed (ROCE).Keywoards: current assets turnover ratio, current ratio, firm performance, inventory turnover ratio, liquidity, profitability, quick ratio, super-quick ratio.